Pengaruh Kesadaran Merek dan Asosiasi Merek Terhadap Keputusan Pembelian Smartphone Oppo (Studi Kasus Konsumen Counter Oppo Plaza Millenium Medan) - Mairani, Farahdilla; Lubis, Nurul Wardani (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study aims to determine the influence of Brand awareness and Brand Associations on Purchasing Decisions on OPPO Smartphones (Case Study of Oppo Plaza Millennium Medan Consumer Counters)". This research uses quantitative methods with non-probability sampling techniques. With a total sample of 108 people who are consumers from the Oppo Plaza Millennium Medan counter. The data collection technique in this research was carried out by distributing questionnaires whose measurements were on a Likert scale and processed statistically using multiple linear regression analysis and hypothesis testing with the t-test, F test, and coefficient of determination (R2), which were previously data. It has been tested using validity, reliability, and classic assumption tests—the data’s processing using the SPSS For Windows 25.0 program. Based on partial hypothesis testing, there is no influence or significance between Brand Awareness and Purchasing Decisions, with a value of count < Tabel, 1.221 < 1.982, and a sig. 0.225 > 0.05. Brand Association positively and significantly influences Purchasing Decisions, with a value of count> Tabel, 7.250 > 1.982, and a sig. 0.000 < 0.05. Furthermore, the research results show that the variables Brand Awareness and Brand Association simultaneously have a positive and significant effect on purchasing decisions. This can be seen from the value of Fcount > FTabel, 49.443 > 2.30, and the sig level. 0.000 < 0.05. The coefficient of determination test shows a value of 0.549, which means that the influence of brand awareness and brand associations on purchasing decisions is 54.9%. In contrast, other variables outside this research influence the rest.